Streptomyces globosus UAE1, a Potential Effective Biocontrol Agent for Black Scorch Disease in Date Palm Plantations - Saeed, Esam E.; Sham, Arjun; Salmin, Zeinab; Abdelmowla, Yasmeen; Iratni, Rabah; El-Tarabily, Khaled; AbuQamar, Synan (Frontiers in Microbiology, 2017)
Many fungal diseases affect date palm causing considerable losses in date production worldwide. We found that the fungicide Cidely® Top inhibited the mycelial growth of the soil-borne pathogenic fungus Thielaviopsis punctulata, the causal agent of black scorch disease of date palm, both in vitro and in vivo. Because the use of biocontrol agents (BCAs) can minimize the impact of pathogen control on economic and environmental concerns related to chemical control, we aimed at testing local actinomycete strains isolated from the rhizosphere soil of healthy date palm cultivated in the United Arab Emirates (UAE) against T. punctulata. The selected isolate can thus be used as a potential agent for integrated disease management programs. In general, the BCA showed antagonism in vitro and in greenhouse experiments against this pathogen. The most promising actinomycete isolate screened showed the highest efficacy against the black scorch disease when applied before or at the same time of inoculation with T. punctulata, compared with BCA or fungicide application after inoculation. The nucleotide sequence and phylogenetic analyses using the 16S ribosomal RNA gene with other Streptomyces spp. in addition to morphological and cultural characteristics revealed that the isolated UAE strain belongs to Streptomyces globosus UAE1. The antagonistic activity of S. globosus against T. punctulata, was associated with the production by this strain of diffusible antifungal metabolites i.e. metabolites that can inhibit mycelial growth of the pathogen. This was evident in the responses of the vegetative growth of pure cultures of the pathogen when exposed to the culture filtrates of the BCA. Altogether, the pathogenicity tests, disease severity indices and mode of action tests confirmed that the BCA was not only capable of suppressing black scorch disease symptoms, but also could prevent the spread of the pathogen, as a potential practical method to improve disease management in the palm plantations. This is the first report of an actinomycete, naturally occurring in the UAE with the potential for use as a BCA in the management of the black scorch disease of date palms in the region.